Acute and long-term sex-dependent effects of social instability stress on anxiety-like and social behaviours in Wistar rats - Graf, Akseli; Murray, Shealin H.; Eltahir, Akif; Patel, Smit; Hansson, Anita C.; Spanagel, Rainer; McCormick, Cheryl M. (Behavioural brain research, 2023)
Adolescence is a critical time of social learning in which both the quantity and quality of social interactions shape adult behavior and social function. During adolescence, social instability such as disrupting or limiting social interactions can lead to negative life-long effects on mental health and well-being in humans. Animal models on social instability are critically important in understanding those underlying neurobiological mechanisms. However, studies in rats using these models have produced partly inconsistent results and can be difficult to generalize. Here we assessed in a sex and age consistent manner the long-term behavioural consequences of social instability stress (SIS - 1-hr daily isolation and change in cage mate between postnatal day (PD30-45)) in Wistar rats. Female and male rats underwent a battery of tests for anxiety-like, exploratory, and social behaviour over five days beginning either in adolescence (PD46) or in adulthood (PD70). Social instability led to reduced anxiety-like behaviour in the elevated plus maze in both sexes in adolescence and in adulthood. Social interactions were also reduced in rats that underwent SIS - an effect that was independent of sex and age when tested. SIS improved social recognition memory in both sexes whereas a sex-dependent effect was seen in the social novelty preference test where male rats that underwent SIS spent more time in social approach toward a novel peer than toward their cage mate. In comparison, control male and female groups did not differ in this test, in time spent with novel versus the cage mate. Thus, overall, social instability stress in Wistar rats altered the behavioural repertoire, with enduring alterations in social behaviour, enhanced exploratory behaviour, and reduced anxiety-like behaviour. In conclusion, the social instability stress paradigm may better be interpreted as a form of enrichment in Wistar rats than as a stressor.